Research priorities in advanced heart failure: James Lind alliance priority setting partnership. Issue 1 (30th June 2020) - Taylor, Clare J; Huntley, Alyson L; Burden, John; Gadoud, Amy; Gronlund, Toto; Jones, Nicholas Robert; Wicks, Eleanor; McKelvie, Sara; Byatt, Kit; Lehman, Richard; King, Anna; Mumford, Bev; et al.
Abstract : Objective: To determine research priorities in advanced heart failure (HF) for patients, carers and healthcare professionals. Methods: Priority setting partnership using the systematic James Lind Alliance method for ranking and setting research priorities. An initial open survey of patients, carers and healthcare professionals identified respondents' questions, which were categorised to produce a list of summary research questions; questions already answered in existing literature were removed. In a second survey of patients, carers and healthcare professionals, respondents ranked the summary research questions in order of priority. The top 25 unanswered research priorities were then considered at a face-to-face workshop using nominal group technique to agree on a 'top 10'. Results: 192 respondents submitted 489 responses each containing one or more research uncertainty. Out-of-scope questions (35) were removed, and collating the responses produced 80 summary questions. Questions already answered in the literature (15) were removed. In the second survey, 65 questions were ranked by 128 respondents. The top 10 priorities were developed at a consensus meeting of stakeholders and included a focus on quality of life, psychological support, the impact on carers, role of the charity sector and managing prognostic uncertainty. Ranked priorities by physicians and patients were remarkably divergent. Conclusions: Engaging stakeholders in setting research priorities led to a novel set of research questions that might not have otherwise been considered. These priorities can be used by researchers and funders to direct future research towards the areas which matter most to people living with advanced HF.